Women's Mental Health A Framework for Its Assessment, Prevention, and Promotion in Health Care Settings - Mento, Carmela; Silvestri, Maria Catena (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Clinical psychology based on gender medicine is a core topic of this Special Issue. In general, consideration of women's mental health is limited; however, it is important to consider subjective wellbeing factors connected with cultural, environmental, epigenetic and personality aspects. Many factors, such as the roles assigned to women nowadays in social and work contexts, can act as predisposing conditions in the etiology of the psychopathological frame, particularly affective disorders. Furthermore, in the developmental life of a woman, important risk factors can be highlighted, such as the vulnerability to psychological distress in women and couples. In particular, the topic addresses the individual maternal requirements for successful transition to healthy motherhood and innovative programs based on gender medicine in the life cycle considering student and elderly experiences. The connection of psychological vulnerability to the environment and repercussions for relationships have been studied in connection with the COVID-19 lockdown, induced changes in women's psychological distress and research regarding sexual arousal, self-image and mental wellbeing. Psychological and emotional forms of violence in couples, such as IPV, is another point highlighting new trend of assessments (i.e., Intimate Partner Violence EAPA-P) and ad hoc treatment in emotional regulation and resilience. Psychological support for women is central to the prevention of psychopathology, especially in relation to subthreshold traits; finally, the topic offers an overview of ad hoc treatments in clinical contexts.